Revisiting the Impact of Density on Social Capital: A Study Case in the Capital City of Indonesia - Usep Nugraha; Rus’an Nasrudin (Department of Development Economics, Universitas Sriwijaya, 2022)
Density is an important indicator closely related to the rate of urbanisation in cities. Density alters social capital, yet the directions of the association remain an open empirical investigation. This study aims to analyse how density and social capital are related in Jakarta, the capital, and the most populous city in Indonesia. Utilising a simple regression and an entropy balance approach to address the selection issue, this study finds that an increase in density of 10 thousand inhabitants per square kilometre is associated with a 2% higher possibility of societies having high social capital. The result is also robust using another definition of social capital and transformation of density variable. A policy recommendation that can be taken based on this study’s results is that the government can design dense urban planning as a model of sustainable urban design, particularly the sustainability in social aspects.